Trapping IgE in a closed conformation by mimicking CD23 binding prevents and disrupts FcεRI interaction - Frederic Jabs (Nature Portfolio, 2018)
IgE is linked to allergic diseases and there is a great interest in developing anti-IgE therapeutics. Here the authors characterize the binding of human IgE Fc to a single domain antibody (sdab) and show that the sdab induces a closed conformation, which prevents and disrupts IgE binding to its receptor FcεRI and abrogates allergen mediated activation.